Enhancement of Jasmonate-Mediated Antiherbivore Defense Responses in Tomato by Acetic Acid, a Potent Inducer for Plant Protection - Chen, Daoqian; Shao, Min; Sun, Shaozhi; Liu, Tingting; Zhang, Hao; Qin, Ningning; Zeng, Rensen; Song, Yuanyuan (Frontiers in Plant Science, 2019)
Acetic acid has been proved as a chemical that could prime the jasmonic acid (JA) signaling pathway for plant drought tolerance. In this study, the capability of acetic acid (AA) for priming of tomato defense against a chewing caterpillar Spodoptera litura and its underlying molecular mechanism were evaluated. AA pretreatment significantly increased tomato resistance against S. litura larvae. Upon larval attack, tomato plants pretreated with AA exhibited increased transcript levels of defense-related genes and elevated activities of polyphenol oxidase and peroxidase, and accumulation of protease inhibitor. Moreover, AA pretreatment resulted in upregulated transcription of JA biosynthesis genes and elevated JA accumulation in tomato seedlings upon insect attack. Furthermore, an apparent loss of AA-induced resistance was observed in a JA pathway-impaired mutant suppressor of prosystemin-mediated responses8 (spr8). These results indicate that AA enhances jasmonate-mediated antiherbivore defense responses in tomato. This raises the possibility of use of acetic acid, a basic and simple biochemical compound, as a promising inducer for management of agricultural pests.